Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

Increasing Hydroclimatic Whiplash Can Amplify Wildfire Risk in a Warming Climate - Daniel L. Swain; John T. Abatzoglou; Christine M. Albano; Manuela I. Brunner; Noah S. Diffenbaugh; Crystal Kolden; Andreas F. Prein; Deepti Singh; Christopher B. Skinner; Thomas W. Swetnam; Danielle Touma (Global Change Biology, 2025)

PINNAL NECROHAEMORRHAGIC DERMATITIS WITH VASCULITIS AND INTRALESIONAL BACTERIA IN RABBITS - G. De Zan; G. De Zottis; I. Brunner; N. Genero; M. Rustico; F. Agnoletti; M. Cocchi (Journal of Comparative Pathology, 2024)

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

Climatic shifts threaten alpine mycorrhizal communities above the treeline - R. Arraiano-Castilho; M.I. Bidartondo; T. Niskanen; I. Brunner; S. Zimmermann; B. Senn-Irlet; B. Frey; U. Peintner; T. Mrak; L.M. Suz (Fungal Ecology, 2024)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Synthetic design hydrographs for ungauged catchments: a comparison of regionalization methods - Manuela I. Brunner; Reinhard Furrer; Anna E. Sikorska; Daniel Viviroli; Jan Seibert; Anne-Catherine Favre (Stochastic Environmental Research and Risk Assessment, 2018)

Iron incorporation in biosilica of the marine diatom Stephanopyxis turris: dispersed or clustered? - Janine Kaden; Stephan I. Brückner; Susanne Machill; Christoph Krafft; Andreas Pöppl; Eike Brunner (BioMetals, 2017)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Soil acidity affects fine root turnover of European beech - A. K. Richter; I. Hajdas; E. Frossard; I. Brunner (Plant Biosystems, 2013)

Fine-root turnover rates of European forests revisited: an analysis of data from sequential coring and ingrowth cores - I. Brunner; M. R. Bakker; R. G. Björk; Y. Hirano; M. Lukac; X. Aranda; I. Børja; T. D. Eldhuset; H. S. Helmisaari; C. Jourdan; B. Konôpka; B. C. López; et al. (Plant and Soil, 2013)

On the emerging role of rabbit as human disease model and the instrumental role of novel transgenic tools - V. Duranthon; N. Beaujean; M. Brunner; K. E. Odening; A. Navarrete Santos; I. Kacskovics; L. Hiripi; E. J. Weinstein; Z. Bosze (Transgenic Research, 2012)

The platform for European root science, COST action E38: An introduction and overview - D. L. Godbold; I. Brunner (Plant Biosystems, 2007)

Tree fine root Ca/Al molar ratio – Indicator of Al and acidity stress - E. I. Vanguelova; Y. Hirano; T. D. Eldhuset; L. Sas-Paszt; M. R. Bakker; Ü. Püttsepp; I. Brunner; K. Lõhmus; D. Godbold (Plant Biosystems, 2007)

Specific root length as an indicator of environmental change - I. Ostonen; Ü. Püttsepp; C Biel; O. Alberton; M. R. Bakker; K. Lõhmus; H. Majdi; D. Metcalfe; A. F. M. Olsthoorn; A. Pronk; E. Vanguelova; M. Weih; et al. (Plant Biosystems, 2007)

Variation in fine root biomass of three European tree species: Beech ( Fagus sylvatica L.), Norway spruce ( Picea abies L. Karst.), and Scots pine ( Pinus sylvestris L.) - L. Finér; H.-S. Helmisaari; K. Lõhmus; H. Majdi; I. Brunner; I. Børja; T. Eldhuset; D. Godbold; T. Grebenc; B. Konôpka; H. Kraigher; M.-R. Möttönen; et al. (Plant Biosystems, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Access of HTB, main metabolite of triflusal, to cerebrospinal fluid in healthy volunteers - M. Valle; M. J. Barbanoj; A. Donner; I. Izquierdo; U. Herranz; N. Klein; H. G. Eichler; M. Müller; M. Brunner (European Journal of Clinical Pharmacology, 2005)

Wood-ash recycling affects forest soil and tree fine-root chemistry and reverses soil acidification - I. Brunner; S. Zimmermann; A. Zingg; P. Blaser (Plant and Soil, 2004)

Molecular markers reveal extensive intraspecific below‐ground overlap of silver fir fine roots - I. BRUNNER; M. RUF; P. LÜSCHER; C. SPERISEN (Molecular Ecology, 2004)
Fine roots are expected to be important determinants of plant competition, but very little is known about the extent of root system overlap. Here, we describe the application of two highly variable plastide microsatellites to study the fine root distribution of tree individuals in a silver fir forest. We demonstrate that the spread of fine roots exceeds the width of above‐ground parts, and that fine root overlaps among neighbouring trees are extensive both laterally and in depth. This approach will help to improve models of below‐ground competition and will facilitate estimations of fine root biomass and thus of below‐ground C pools.

Wood ash treatment affects seasonal N fluctuations in needles of adult Picea abies trees: a 15 N-tracer study - M. Jggi; R. Siegwolf; M. Genenger; D. Hallenbarter; I. Brunner; J. Fuhrer (Trees, 2004)

Fine root growth and element concentrations of Norway spruce as affected by wood ash and liquid fertilisation - M. Genenger; S. Zimmermann; D. Hallenbarter; W. Landolt; E. Frossard; I. Brunner (Plant and Soil, 2003)

Rapid 15N uptake and metabolism in fine roots of Norway spruce - M. Genenger; M. Jaeggi; R. Siegwolf; M. Chalot; E. Frossard; I. Brunner (Trees, 2003)

Molecular identification of fine roots of trees from the Alps: reliable and fast DNA extraction and PCR–RFLP analyses of plastid DNA - I. Brunner; S. Brodbeck; U. BÜchler; C. Sperisen (Molecular Ecology, 2001)
Fine roots of trees are intensively used as indicators to assess soil alterations, e.g. those owing to atmospheric inputs of acidifying substances, but their identification to species with morphological criteria is difficult. In this study, we established molecular techniques in order to identify fine roots of the 30 most common tree species of the Alps. We developed a protocol for efficient isolation of DNA from fine roots with extraction of DNA in the presence of polyvinylpyrrolidone (PVP) and polyvinylpolypyrrolidone (PVPP). The trn L (UAA) intron of plastid DNA was used as a marker for fine root identification. We amplified and sequenced this intron with plant universal primers. The size of the sequences ranged from 444 to 672 bp . A synoptic key for species identification was designed on the basis of restriction fragment patterns predicted from sequence data. Using the restriction enzyme Taq I as key enzyme, and where necessary Hin fI, Rsa I and Cfo I, 16 taxa, including Picea abies , Larix decidua , Abies alba , and Fagus sylvatica , the dominant tree species of the Alpine region could be identified by agarose gel electrophoresis of restriction fragments. Fourteen taxa could be identified to the genus level, among them Quercus , Salix and Populus species. In a field study, conducted in a 20 × 30 m plot of a mixed forest with five tree species, fine roots of 43 out of 46 samples were identified and their distributions were mapped. These results demonstrate the utility of our DNA extraction method and of the trn L intron for the identification of fine tree roots.

Refined mapping of the gene for autosomal dominant retinitis pigmentosa (RP17) on chromosome 17q22 - A. I. den Hollander; S. D. van der Velde-Visser; Alfred J. L. G. Pinckers; Carel B. Hoyng; Han G. Brunner; Frans P. M. Cremers (Human Genetics, 1999)